Incidence and Associated Factors of Weight Gain During the Covid-19 Pandemic - Daniel, Marina Martins; Liboredo, Juliana Costa; Anastácio, Lucilene Rezende; Souza, Tamires Cássia de Melo; Oliveira, Lívya Alves; Della Lucia, Ceres Mattos; Ferreira, Lívia Garcia (Frontiers in Nutrition, 2022)
The behavioral changes that arose from quarantine due to the COVID-19 pandemic may have impacted on people’s weight. The aim of this observational study was to investigate the incidence and associated factors of weight gain during the quarantine period in Brazil. An online survey was performed during August and September, 2020. Participants recorded their current and usual weight before the implementation of prophylactic measures of social isolation. A multivariate logistic regression model was performed in order to identify associated factors of weight gain. Data on 1334 participants were evaluated (33.6y, 79.8% females). The difference of weight was 1.34kg (-9.0 to +30.0kg) and 58.8% of participants have gained weight during the period (3.0kg; 0.1 to 30.0kg). Associated factors of weight gain were increased food intake (OR=5.405); increased snacking (OR=2.860); eneving snack (OR=1.538); time spent at work, including household chores (OR=1.581); higher frequency of alcoholic beverage intake (OR=1.589); higher dose of alcoholic beverage (OR=1.109); increased fast food (OR=1.107); and canned products in relation to the period prior to the pandemic period (OR=1.077); uncontrolled eating (OR=1.010); physical activity before pandemic period (OR=0.997); increase in physical activity (OR=0.997) and vegetable intake (OR=0.923) in relation to the period prior to the pandemic. Most participants have gained weight during the pandemic because of working changes, lifestyle, eating habits changes, and uncontrolled eating behavior. These results can be useful to encourage changes during future quarantine periods in order to prevent weight gain.